ANALISIS SIFAT OPTIK LAPISAN TIPIS BILAYER ZnO/TiO2 YANG DIDEPOSISIKAN MENGGUNAKAN METODE SOL-GEL SPRAY COATING DAN APLIKASINYA SEBAGAI FOTODEGRADASI ZAT WARNA - Hanum Yuda Aditya; Heri Sutanto (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
ZnO/TiO2 bilayer thin films have been deposited on a glass substrate by using sol-gel method with spin coating technique. The quality of films deposited on buffer layer is found to be superior to those grown directly on a substrate. The ability of photodegradation of ZnO/TiO2 was observed through the dye test by various molarities of ZnO solution. ZnO sol was prepared by dissolving zinc acetate dehydrate into a solvent of isopropanol then add monoethanolamine and stirred for 30 min at 70°C. For preparing TiO2 sol, titanium tetraisopropoxide is first dissolved in a mixture containing isopropanol and ethanol at room temperature. Then after 30 min stirring, the sol was titrated with a mixture of acetic acid, ethanol and deionized water. The process was followed by 60 min at room temperature. ZnO sol as a first layer is first deposited on a glass substrate and then proceed TiO2 sol on it, for the both deposition was heated at 450oC. The optical properties of ZnO/TiO2 bilayer thin films was characterized by using spectrophotometer UV-Vis. The results showed that the molarity of the ZnO sol affects the optical properties of ZnO/TiO2 bilayer thin films. The band gap energy of the ZnO/TiO2 bilayer thin films with different molarity of ZnO sol respectively 0,1 M, 0,3 M, 0,5 M and 0,7 M has been measured about 3,21 eV, 3,27 eV, 3,32 eV and 3,36 eV. The results of the photodegradation test of the ZnO/TiO2 bilayer thin films have been able degrade methylene blue up to 99,85%, methyl orange 50,68% and batik’s dye 49,87%.Keywords: sol-gel, spray coating, photocatalist, ZnO/TiO2, band gap energy